The Role of the Size of the Small Group and Informal Subgroups in Intragroup Conflicts - Andrey V. Sidorenkov; Eugene F. Borokhovski (Behavioral Sciences, 2020)
This study examines the relationship between (a) the size of groups and the number of informal subgroups in them with conflicts in the context of the group, and (b) the size of the informal subgroups with conflicts in the context of the subgroup. A multidimensional model of intragroup conflict was used, which includes two dimensions: five levels of conflict (i.e., interpersonal (individual–individual), micro-group (individual–subgroup), group (individual–group), subgroup–subgroup, and subgroup–group) and two types of conflict (activity-oriented and subject-oriented). Each level of conflict contains two types. Forty-one small work groups (334 employees) took part in the study. In the group as a whole, both the size of the group and the number of informal subgroups in it have a positive relationship with subgroup–subgroup conflict in both types and subgroup–group subject-oriented conflict, and have a negative connection with micro-group subject-oriented conflict. In turn, the size of the subgroup is positively associated with the two types of subgroup–group conflict and negatively connected with the two types of micro-group conflict, as well as with interpersonal activity-oriented conflict at the level of the informal subgroup.